2019
DOI: 10.3390/ijms20051033
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Curcumin and Its Derivatives as Anticancer Agents

Abstract: Cancer is the second leading cause of death in the world and one of the major public health problems. Despite the great advances in cancer therapy, the incidence and mortality rates of cancer remain high. Therefore, the quest for more efficient and less toxic cancer treatment strategies is still at the forefront of current research. Curcumin, the active ingredient of the Curcuma longa plant, has received great attention over the past two decades as an antioxidant, anti-inflammatory, and anticancer agent. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
402
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 663 publications
(468 citation statements)
references
References 140 publications
1
402
0
4
Order By: Relevance
“…13 C NMR spectrum of Compound 3 in CDCl 3 as solvent.4.1.3. (1E,6E)-1-(4-hydroxy-3-methoxyphenyl)-7-[3-methoxy-4(4-methylbromobenzyl)oxyphenyl]hepta-1,6-diene-3,5-dione (4) and (1E,6E)-1,7-bis [3-methoxy-4(4-methylbromobenzyl) oxyphenyl]hepta-1,6-diene-3,5-dione(5) …”
mentioning
confidence: 99%
“…13 C NMR spectrum of Compound 3 in CDCl 3 as solvent.4.1.3. (1E,6E)-1-(4-hydroxy-3-methoxyphenyl)-7-[3-methoxy-4(4-methylbromobenzyl)oxyphenyl]hepta-1,6-diene-3,5-dione (4) and (1E,6E)-1,7-bis [3-methoxy-4(4-methylbromobenzyl) oxyphenyl]hepta-1,6-diene-3,5-dione(5) …”
mentioning
confidence: 99%
“…In fact, the glucuronidation and sulfation of curcumin happen very soon after in vivo administration and the produced metabolites are rapidly excreted from feces, urine and bile [57]. To have an idea of the low bioavailability of curcumin, these data are very indicative: ingestion of 2 g of pure curcumin results in the presence of only 10 ng/mL curcumin in plasma [58]. Indeed, its poor bioavailability and high potential to interfere with other drugs constitute real obstacles for precisely defining the real biological and clinical anti-cancer properties of curcumin.…”
Section: Laboratory and Clinical Studies Carried Out On The Effects Omentioning
confidence: 99%
“…In this regard, numerous attempts aimed at increasing the efficacy and bioavailability of curcumin have been made. In particular, attention has been paid to designing suitable formulations using nanocarriers for delivery and targeting [58][59][60].…”
Section: Laboratory and Clinical Studies Carried Out On The Effects Omentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has shown that natural plant compounds (NPCs), such as curcumin, resveratrol and dictamnine, have significant clinical benefits in cancer, such as inhibiting cell proliferation, affecting the cell cycle, and promoting apoptosis and/or autophagy (6)(7)(8). In addition, bioactive natural components extracted from plants have received attention for their inhibition of epithelial-mesenchymal transformation (EMT) through anti-inflammatory, anti-fibrosis or anti-oxidant mechanisms (9).…”
Section: Introductionmentioning
confidence: 99%